Effect of Rice GDP-L-Galactose Phosphorylase Constitutive Overexpression on Ascorbate Concentration, Stress Tolerance, and Iron Bioavailability in Rice - Broad, Ronan C.; Bonneau, Julien P.; Beasley, Jesse T.; Roden, Sally; Sadowski, Pawel; Jewell, Nathaniel; Brien, Chris; Berger, Bettina; Tako, Elad; Glahn, Raymond P.; Hellens, Roger P.; Johnson, Alexander A. T. (Frontiers in Plant Science, 2020)
Ascorbate (vitamin C) is an essential multifunctional molecule for both plants and mammals. In plants, ascorbate is the most abundant water-soluble antioxidant that supports stress tolerance. In humans, ascorbate is an essential micronutrient and promotes iron absorption in the gut. Engineering crops with increased ascorbate levels has the potential to improve both crop stress tolerance and human health. Here, rice (Oryza sativa L.) plants were engineered to constitutively overexpress the rice GDP-L-galactose phosphorylase coding sequence (35S-OsGGP) which encodes the rate-limiting enzymatic step of the L-galactose pathway. Ascorbate concentrations were negligible in both null segregant and 35S-OsGGP brown rice but significantly increased in 35S-OsGGP germinated brown rice relative to null segregant. Foliar ascorbate concentrations were significantly increased in 35S-OsGGP plants in the vegetative growth phase relative to null segregant, but significantly reduced at the reproductive growth phase and were associated with reduced OsGGP transcript levels. The 35S-OsGGP plants did not display altered salt tolerance at the vegetative growth phase despite having elevated ascorbate concentrations. Ascorbate concentrations were positively correlated with ferritin concentrations in Caco-2 cells—an accurate predictor of iron bioavailability in human digestion—exposed to in vitro digests of null segregant and 35S-OsGGP brown rice and germinated brown rice samples.